2017
DOI: 10.1590/1678-7757-2016-0147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inhalation therapy on the incidence of carious lesions in patients with asthma and COPD

Abstract: Objective:The aim of this study was to investigate the incidence of carious lesions, the amount of salivary flow rate and pH value in patients with asthma and chronic obstructive pulmonary diseases (COPD), using inhalation therapy. The obtained results were compared with the results of adult healthy subjects, forming a control group.Material and Methods:The study included 80 participants aging between 18 and 65 years. The experimental group (EG) was comprised of 40 participants, previously diagnosed with asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
0
19
0
4
Order By: Relevance
“…[1][2][3] Bronchial asthma is considered a chronic inflammatory airway disorder that mostly affects pediatric patients, up to 10-15 % of males and 7-10 % of females. 4,5 It is known that asthma may lead to a higher prevalence of dental caries due to different biological mechanisms, such as direct changes in salivary composition or indirect changes caused by inhaled bronchodilator use (beta 2 adrenergic agonists, anticholinergics, and other similar acting agents). The administration of inhaled drugs alters saliva quality and quantity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Bronchial asthma is considered a chronic inflammatory airway disorder that mostly affects pediatric patients, up to 10-15 % of males and 7-10 % of females. 4,5 It is known that asthma may lead to a higher prevalence of dental caries due to different biological mechanisms, such as direct changes in salivary composition or indirect changes caused by inhaled bronchodilator use (beta 2 adrenergic agonists, anticholinergics, and other similar acting agents). The administration of inhaled drugs alters saliva quality and quantity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many inhaled drugs have sugar as an excipient, which serves as a substrate for cariogenic bacteria and alters the oral pH. [4][5][6][7] Beta 2 agonists activate beta 2 receptors in the salivary g l a n d s , t h u s p r o m o t i n g c y c l i c adenosine monophosphate (cAMP) production, which reduces salivary secretion and protein synthesis. In addition, only 10-20 % of these drugs reach the lower airways; the rest remain at the oropharynx and upper airways level, so they serve as a substrate for cariogenic bacteria and alter the oral pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alavaikko et al 16) reported of doubling of the risk of dental caries in asthma patients, and doctors and dentists emphasized the need to develop dental caries prevention programs for asthma patients. Bozejac et al 17) reported that asthma patients had no oral health education, and Ryberg et al 18) suggested that asthma patients have increased susceptibility to dental caries but poor oral hygiene management. In order to prevent poor oral health in asthma patients, it is necessary to educate them regarding the importance of oral health, aid them with appropriate oral health management, and develop programs to prevent oral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Además, el tratamiento inhalatorio con agonistas β2 y corticoesteroides reduce la tasa de secreción salival, disminuye el pH y altera la composición salival. Como lo reportado por Bozejac et al (21) , quienes encontraron que los pacientes con asma moderado persistente y en tratamiento de más de cinco años con diferentes combinaciones de inhaladores como salmeterol + fluticasona, budesonida + formoterol, beclometasona + formoterol y bromuro de ipratopio + fenoterol redujeron significativamente la tasa de secreción salival (0,279 mL/min) en comparación a los pacientes sanos (0,496 mL/min); p=0,001. Alavaikko et al (22) en su revisión sistemática evidenciaron una asociación significativa entre el asma y la caries dental para la dentición primaria (OR=2,73; IC95%: 1,61 -4,64) y permanente (OR=2,04; IC95%: 1,44 -2,89).…”
Section: Discussionunclassified